Restorative Justice as a Law Enforcement Policy Instrument: An Analysis of Implementation in the West Java Regional Police: Keadilan Restoratif sebagai Instrumen Kebijakan Penegakan Hukum: Analisis Implementasi di Kepolisian Daerah Jawa Barat - Bahriyah, Amalina Zukhrufatul; Kamarusdiana; Asmawi; Alfitra (Al-Jinayah : Jurnal Hukum Pidana Islam, 2025)
This study examines the application of restorative justice in the criminal justice system, particularly within the West Java Regional Police, in light of Police Regulation No. 8 of 2021, and the factors that support and hinder its success. The paradigm shift from retributive justice to restorative justice aims to create a more humane legal system oriented toward restoring social relations. This study uses a qualitative method through an empirical legal approach. The study's results indicate that the application of restorative justice by the West Java Regional Police is reasonably practical in resolving conflicts peacefully, restoring victims' losses, and maintaining social harmony. It still faces challenges, including inconsistent enforcement by law enforcement officers, a lack of public understanding, and technical obstacles to restitution.